Optimisation of alginate-pectin bead formulation using central composite design guided electrospray technique - Azhar, Muhammad Fitri; Haris @ Harith, Muhammad Salahuddin; Mohamad, Izzuddin; Noor Ismadi, Muhammad Nur Shafiq; Abu Yazid, Anis Afiful Huda; Rahman, Siti Radziah; Mohd Azlan, Nur Hakimah (Universiti Putra Malaysia, 2020)
Alginate-pectin beads act as a carrier in improving the oral bioavailability of bioactive compounds. Electrospray technique facilitates the production of uniform size and shape of alginate-pectin beads. Interaction between key electrospray process parameters affects the size and shape of the beads. A proper model should be employed to establish these correlating interactions. In this study, the electrospray technique was guided with a central composite design (CCD) and response surface methodology (RSM). One quadratic and one linear model were obtained for size and the sphericity coefficient, respectively. The CCD-RSM empirical model derived from this study is essential to determine significant factors and their levels in producing beads with consistent size and sphericity coefficient. The results indicate that the applied voltage has the most significant influence on size, while the alginate-pectin concentration is the most prominent factor in producing spherical beads. The quite spherical beads with a minimum size of 2.97 mm were obtained at an alginate-pectin concentration of 3.5%, a flow rate of 10.0mL/h, an applied voltage of 2.4 kV, and a distance between the nozzle and the gelation bath of 16.0 cm.